Preparation and ionic conductive properties of all‐solid polymer electrolytes based on multiarm star block polymers. Issue 3 (26th November 2012) - Ren, Shitong; Chang, Hefei; He, Lijuan; Dang, Xiaofei; Fang, Yanyan; Zhang, Liaoyun; Li, Huayi; Hu, Youliang; Lin, Yuan
Abstract A series of star block polymers with a hyperbranched core and 26 arms are successfully synthesized by atom transfer radical polymerization of styrene (St), and poly(ethylene glycol) methyl ether methacrylate from a hyperbranched polystyrene (HBPS) multifunctional initiator. All‐solid polymer electrolytes composed of these multiarm star polymers and lithium salts are prepared. The influences of polyoxyethylene (PEO) side‐chain length, PEO content, lithium salt concentration and type, and the structure of polymer on ionic conductivity are systematically investigated. The resulting polymer electrolyte with the longest PEO side chains exhibits the best ionic conductive properties. The maximum conductivity is 0.8 × 10−4 S cm−1 at 25°C with EO/Li = 30. All the prepared multiarm star block polymers possess good thermal stability. The mechanical property is greatly improved owing to the existence of polystyrene blocks in the multiarm star polymer molecules, and flexible films can be obtained by solution‐casting technique. © 2012 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013